قياس مبادرة النمو الشخصي لدى طلبة الجامعة - ستار عبدالرضا العادلي علي; حسن محمد نمير (مجلة كلية التربية, 2020)
The Personal Growth Initiative refers to the process of personal growth rather than the outcome of an individual’s efforts to change. This skill set consists of individuals’ willingness to change themselves, how individuals apply knowledge to plan and implement self-change, and individuals’ desire for change (Robitschek et al., 2012). Cluster random sample was used to include 400 participants 147 0f them ware males while the rest which was 253 ware females. The researcher translated the scale from English to Arabic and included the personal growth initiative scale. The study included 16 item based on the PGI theory. Extracted Validity and Reliability of the scale, the used one sample. The used one sample, and the results showed that the university students ware personal growth initiative, Descriptive reason has been used to achieve the aims of the present study.